Adeno-Associated Virus Serotype 8-Mediated Genetic Labeling of Cholangiocytes in the Neonatal Murine Liver - Sanghoon Lee; Ping Zhou; Senyo Whyte; Soona Shin (MDPI AG, 2020)
Determination of the cellular tropism of viral vectors is imperative for designing precise gene therapy. It has been widely accepted that transduction of hepatocytes using adeno-associated virus serotype 8 (AAV8) is a promising approach to correct inborn errors in neonates, but the type of neonatal hepatic cells transduced by AAV8 has not been thoroughly investigated. To address this question, we used a reporter mouse that carries Cre recombinase (Cre)-inducible yellow fluorescent protein (YFP). Our analysis primarily focused on cholangiocytes, given their pivotal roles in normal liver function and disease. We treated RosaYFP/+ mice at postnatal day 2 (P2) with AAV8-cytomegalovirus (CMV) promoter-Cre and analyzed livers at P10 and P56. The vast majority of HNF4α+ hepatocytes were labeled with YFP at both time points, and 11.6% and 24.4% of CK19+ cholangiocytes were marked at P10 and P56, respectively. We also detected YFP+ cells devoid of hepatocyte and cholangiocyte markers, and a subset of these cells expressed the endothelial and fibroblast marker CD34. Next, we used the hepatocyte-specific thyroxine-binding globulin (TBG) promoter. Surprisingly, AAV8-TBG-Cre marked 6.8% and 30.9% of cholangiocytes at P10 and P56, respectively. These results suggest that AAV8 can be a useful tool for targeting cholangiocytes in neonatal livers.